Genes, genesis and God: Holmes Rolston III: Richard J. Burke lecture in philosophy, religion and society - Rolston, Holmes, 1932-2025, speaker; Burke, Richard J., speaker (Colorado State University. Libraries, 2006)
Holmes Rolston delivers the inaugurating Richard J. Burke Lecture in Philosophy, Religion and Society at Oakland University, Rochester, Michigan on March 13, 2006. Professor Rolston discusses the debate about order and disorder, randomness and probability, actualities and possibilities, as these result in increasing diversity and complexity over the evolutionary epic. He features the increasing information in genes that appears in natural history, resulting in genetic coding, eucaryotes, sexuality, societies, and mind, with human capacities for culture, including science, religion and ethics. Life opens up increasingly new possibility space. In both nature and culture, life gets more promise, becomes more promising. Life is self-transforming, takes on meaning. This invites and demands deeper explanations, philosophically and theologically.
Audio out of sync with video.
To request a transcript, please contact library_digitaladmin@mail.colostate.edu or call (970) 491-1844.
Keywords: science; religion; natural history